Thermal Activation of Bagasse Ash in High Strength Portland Cement Mortar: Thermal Activation of Bagasse Ash in Mortar - Amin, Noor-ul- (Biological Sciences - PJSIR, 2010)
The pozzolonic reactivity of bagasse ash was enhanced using thermal activation technique by curing mortar specimens containing bagasse ash, at 20, 40 and 60 °C and the samples were tested for compressive strength at the age of 3, 7 and 28 days. Results indicated that bagasse ash is very sensitive to temperature rise and thus the application of thermal activation is very useful when early age strength development is desired. Bagasse replacement by 30% at 40 °C and 60 °C increased the mortar strength at 7 days by 10 and 18% more than the control, respectively.